Exploring the Impact of Agritourism Integrated Restaurants on the Culinary Tourism Experience in Goa (Journal of Informatics Education and Research, 2024)
This study examines the impact of agritourism on culinary tourism in Goa, emphasizing authenticity and cultural integration. Four variables were analyzed: the frequency of agritourism activities, restaurant involvement, local cultural integration, and authenticity. The results show that while the frequency of activities and restaurant participation have little effect, the integration of local culture and authenticity significantly enhance the culinary experience. Authenticity emerged as the most influential factor, greatly enriching tourists' experiences. The study suggests that to maximize agritourism's impact on culinary tourism, the focus should be on providing authentic, culturally integrated experiences rather than increasing the number of activities. These findings are essential for developing more engaging and meaningful agritourism offerings in Goa.